Fostering Hope and Resilience Through Children’s Literature (LEARNing Landscapes, 2023)
Significant traumatic events affect communities and schools. Teachers need tools to help navigate challenging conversations with their students. Consequently, we utilized our children’s literature course on the use of picture books that would invite dialogue supporting children responding to traumatic events. Specifically, we reconceptualized an existing read-aloud assignment to focus on selecting and using literature that facilitates children’s responses to challenging life experiences. This article describes the read-aloud assignment, providing a content analysis of the books the preservice teachers selected, and examples of both preservice teachers’ responses and K-12 students’ responses to the literature.
Keywords: literature; trauma; preservice teacher; teacher education